Book review of: Kloke, A.; Monheim, H.; Paetzel, U. (Hrsg.) (2023): Karl Ganser. Integratives Planen und Handeln - Hesse, Markus (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
Book review